Prediction of passive intermodulation arising from corrosion - Abuelma’atti, M.T. (2003)
Large-signal analysis of a corroded interface subjected to multisinusoidal signals is presented. The special cases of sinusoids with sufficiently small amplitudes and three equal-amplitude sinusoids are considered in detail, and the results are compared, whenever possible, with previously published results.